Pengembangan dan Validasi Instrumen Pilihan Karier Siswa (IPKS): Analisis Model RASCH - Handani, Tri; Supriatna, Mamat; Yudha, Eka Sakti (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2023)
Career choice is an individual's ability to determine one of several choices related to a future career. The evaluation of career choice instruments helps students in determining their career choices based on their personality and potential. However, the limitations of career choice instruments encourage researchers to develop career choice instruments that measure students' abilities to determine the direction of their career choices. This study aims to develop and validate a career choice instrument using the RASCH model. The participants in this study were 213 students (100 males and 113 females) at the senior high school level aged 14-16 years (mean=0.80 and SD=0.83). The results showed that Cronbach's Alpha was in the very good category (0.83). The reliability value of people is in a good category (0.83) and the reliability of goods is in a special category (0.98). 58 statement items developed after being tested for validity and reliability, 55 statement items are appropriate for measuring student career choices, especially in Indonesia.